Lasers in dentistry : guide for clinical practice - Freitas, Patricia M. de; Simoes, Alyne (Ames, Iowa, USA : John Wiley & Sons, Inc., 2015)
'Lasers have become an increasingly useful tool in conventional dental practice. Their precision and less invasive quality make them an attractive technology in esthetic and pediatric dentistry, oral medicine, and a range of other dental procedures. Lasers in Dentistry: Guide for Clinical Practice is a comprehensive, yet concise and easy-to-use guide to integrating lasers into conventional clinical practice.The book begins by providing the reader a thorough understanding of how lasers work and their varied effects on oral tissues. Subsequent chapters are organized by procedure type, illustrating common clinical techniques with step-by-step illustrations and case examples. In addition, each chapter provides an overview of the latest research for use in clinical practice. More comprehensive than at atlas yet practical and clinically oriented in its approach, Lasers in Dentistry is an essential tool for practitioners and students looking to broader their skill set in laser dentistry'--Provided by publisher.
Basic Principles of Lasers and LEDs -- Physics of lasers and LEDs : Basic concepts / Clovis Grecco, et al. -- High power lasers and their interaction with biological tissues / Denise Maria Zezell and Patricia Aparecida Ana -- Low power lasers : Introduction / Maria Cristina Chavantes, Martha Simoes Ribeiro, and Nathali Cordeiro Pinto -- Cellular mechanisms of photobiomodulation / Tiina I. Karu -- Low level laser therapy - mechanism of action : Inflammatory process / Jan Magnus Bjordal, et al. Low level laser therapy - mechanism of action : Analgesia / Roberta Chow -- Antimicrobial photodynamic therapy in dentistry / Felipe E Sperandio, et al. Dosimetry / Jan Tuner, Martha Simoes Ribeiro, and Alyne Simoes -- Risk management and the safe use of laser technology / Rosely Cordon and Dalva Cruz Laqana -- Preventive, Esthetic, and Restorative dentistry -- Selective caries removal, cavity preparation and adhesion to irradiated tissues / Patricia M. de Freitas, et al. -- Management of non-carious cervical lesions / Ana Cecilia Correa Aranha, Karen Muller Ramalho, and Marcella Esteves-Oliveira -- Antimicrobial photodynamic therapy for carious tissue / Giselle Rodrigues de SantAnna and Danilo Antonio Duarte -- Treatment of internal ceramic surfaces / Carlos de Paula Eduardo, Marina Stella Bello-Silva, and Paulo Francisco Cesar -- Dental bleaching with LEDs and lasers / Fatima Zanin, Aldo Brugnera Jr, and Mateus Costola Windlin -- Caries diagnosis / Mariana Minatel Braga, et al. -- Lasers in caries prevention / Lidiany Karla Azevedo Rodrigues, Patricia M. de Freitas, and Marines Nobre-dos-Santos -- Endodontics -- Bacterial reduction in root canals using antimicrobial photodynamic therapy / Aguinaldo S. Garcez and Silvia C. Nunez -- High power lasers in apical surgery / Sheila C. Gouw-Soares, Jose Luiz Lage-Marques, and Claudia Strefezza -- High power lasers in endodontics / Jose Luiz Lage-Marques, Sheila C. Gouw Soares, and Claudia Strefezza -- Periodontology -- Surgical and non-surgical treatment of periodontal diseases / Leticia Helena Theodoro and Valdir Gouveia Garcia -- Antimicrobial photodynamic therapy in the treatment of periodontal diseases / Valdir Gouveia Garcia and Leticia Helena Theodoro -- Esthetic treatment of gingival melanin hyperpigmentation with the Er:YAG laser / Daniel Simoes A. Rosa and Akira Aoki -- Oral surgery -- Lasers in soft tissues surgeries / Luciane Hiramatsu Azevedo, Marines Sammamed Freire Trevisan, and Ana Maria Aparecida de Souza -- Implantodontology / Juliana Marotti and Georgios E. Romanos -- Bone biomodulation / Antonio Luiz Barbosa Pinheiro, et al. -- Use of low level laser therapy in lymphatic drainage for edema / Luciana Almeida-Lopes and Attilio Lopes -- Orthodontics and Orofacial Pain -- Temporomandibular disorders / Caroline Maria Gomes Dantas and Carolina Lapaz Vivan -- Low level lasers in orthodontics / Marines Vieira S. Sousa -- Traditional Chinese medicine and laser therapy / Mario Pansini, Fabiano Augusto Sfier de Mello, and Andrea Malluf Dabul de Mello -- Treatment of Oral and Facial Lesions Papilloma and fibroma / Luiz Alcino Guerios, et al. -- Hemangioma and lymphangioma / Luciane Hiramatsu Azevedo and Claudia Strefezza -- Non-neoplastic proliferative lesions or soft tissue tumor-like lesions of the oral cavity / Vivian Cunha Galletta Kern, et al. -- Oral mucocele / Luciana Correa and Luciane Hiramatsu Azevedo -- Potentially malignant disorders of the oral mucosa / Vivian Cunha Galletta Kern, et al. -- Herpes / Juliana Marotti -- Recurrent aphthous ulcers / Leila Soares Ferreira and Daiane Thais Meneguzzo -- Burning mouth syndrome / Lucia de Fatima Cavalcanti dos Santos and Jair Carneiro Leao -- Nerve repair by light / Felipe F. Sperandio, et al. -- Laser and Antimicrobial Photodynamic Therapies in Cancer Patients -- Optical diagnosis of cancer and potentially malignant lesions / Cristina Kurachi, Lilian Tan Moriyama, and Alessandro Cosci -- Low level laser therapy in the prevention and treatment of oral mucositis / Alyne Simoes, et al. -- Cost-effectiveness of laser therapy in hospital practice / Leticia Mello Bezinelli and Luciana Correa -- Low Level Laser Therapy for hyposalivation and xerostomia / Alyne Simoes, et al. -- Antimicrobial photodynamic therapy in cancer patients / Luana de Campos, Cesar A. Migliorati, and Alyne Simoes -- Photodynamic therapy in cancer treatment / Juliana Ferreira-Strixino and Elodie Debefve.
Includes bibliographical references and index.
Keywords: Laser Therapy -- methods; Oral Surgical Procedures -- instrumentation; Dentistry -- methods; Stomatognathic Diseases -- therapy